A review on phytochemical, pharmacological, and pharmacognostical profile of Wrightia tinctoria: Adulterant of kurchi - Srivastava, Rajani (Pharmacognosy Reviews)
Wrightia tinctoria R. Br. belongs to family Apocynaceae commonly called as Sweet Indrajao, Pala Indigo Plant, Dyer’s Oleander. “Jaundice curative tree” in south India. Sweet Indrajao is a small, deciduous tree with a light gray, scaly smooth bark. Native to India and Burma, Wrightia is named after a Scottish physician and botanist William Wright (1740‑1827). Sweet Indrajao is called dhudi (Hindi) because of its preservative nature. The juice of the tender leaves is used efficaciously in jaundice. Crushed fresh leaves when filled in the cavity of decayed tooth relieve toothache. In Siddha system of medicine, it is used for psoriasis and other skin diseases. Oil 777 prepared out of the fresh leaves of the plant has been assigned to analgesic, anti‑inflammatory, and anti‑pyretic activities and to be effective in the treatment of psoriasis. The plant is reported to contain presence of flavanoid, glycoflavones‑iso‑orientin, and phenolic acids. The various chemical constituents isolated from various parts of the plant are reported as 3,4‑Seco‑lup‑20 (29)‑en‑3‑oic acid, lupeol, stigmasterol and campetosterol, Indigotin, indirubin, tryptanthrin, isatin, anthranillate and rutin Triacontanol, Wrightial, cycloartenone, cycloeucalenol, β‑amyrin, Alpha‑Amyrin, and β‑sitosterol, 14α‑methylzymosterol. Four uncommon sterols, desmosterol, clerosterol, 24‑methylene‑25‑methylcholesterol, and 24‑dehydropollinastanol, were isolated and identified in addition to several more common phytosterols. The Triterpinoids components of the leaves and pods of Wrightia tinctoria also isolated. This article intends to provide an overview of the chemical constituents present in various parts of the plants and their pharmacological actions and pharmacognostical evaluation.
Keywords: Anti‑viral; aristolactams; Houttuynia cordata; Saururaceae; Pharmacology; phytochemicals; therapeutic uses; wrightia tinctoria